The Correlation between University Students' Personality and Mastery of Writing Skills - Panggih Rahardi; Vina Oktaviana; Tri Himatul Aliyah; Afi Normawati (SAGA: Journal of English Language Teaching and Applied Linguistics, 2024)
This study seeks to examine whether university students' personalities and writing skills are correlated. This study used correlational research as its methodology. The researchers examined two variables, university students' personality and writing skills, to establish a statistical correlation between them. This study's respondent sample consists of forty students majoring in English education. This study was conducted in the English Education Department of Universitas Tidar's Faculty of Teacher Training and Education. Using an International Personality Item Pool (IPIP) questionnaire makes it simple to ascertain the personality scores of each respondent, regardless of whether they are high-extroversion or low-extroversion learners. In addition, the participants' writing skills were shown by their mid-semester essay writing course test scores. Quantitative data exists for both extroversion and writing scores. Therefore, Pearson product-moment and SPSS were used to analyze the data. Based on the results of this study, the researchers conclude that there is only a weak correlation between university students' personalities and their mastery of writing skills. Because the findings of this study contrast with those of other studies, it is hoped that further research will be conducted to provide a more nuanced and comprehensive understanding.